Comparative Metagenomic Analysis of Electrogenic Microbial Communities in Differentially Inoculated Swine Wastewater-Fed Microbial Fuel Cells. (12th October 2017) - Khilyas, Irina V.; Sorokin, Anatoly A.; Kiseleva, Larisa; Simpson, David J. W.; Fedorovich, V.; Sharipova, Margarita R.; Kainuma, Mami; Cohen, Michael F.; Goryanin, Igor
Abstract : Bioelectrochemical systems such as microbial fuel cells (MFCs) are promising new technologies for efficient removal of organic compounds from industrial wastewaters, including that generated from swine farming. We inoculated two pairs of laboratory-scale MFCs with sludge granules from a beer wastewater-treating anaerobic digester (IGBS) or from sludge taken from the bottom of a tank receiving swine wastewater (SS). The SS-inoculated MFC outperformed the IGBS-inoculated MFC with regard to COD and VFA removal and electricity production. Using a metagenomic approach, we describe the microbial diversity of the MFC planktonic and anodic communities derived from the different inocula. Proteobacteria (mostly Deltaproteobacteria) became the predominant phylum in both MFC anodic communities with amplification of the electrogenic genus Geobacter being the most pronounced. Eight dominant and three minor species of Geobacter were found in both MFC anodic communities. The anodic communities of the SS-inoculated MFCs had a higher proportion of Clostridium and Bacteroides relative to those of the IGBS-inoculated MFCs, which were enriched with Pelobacter . The archaeal populations of the SS- and IGBS-inoculated MFCs were dominated by Methanosarcina barkeri and Methanothermobacter thermautotrophicus, respectively. Our results show a long-term influence of inoculum type on the performance and microbial community composition of swine wastewater-treating MFCs.